Rancang Bangun Lengan Robot Berbasis Arduino Menggunakan Sistem Kontrol Sensor Giroskop - Adriana Siregar , Lisa; Ananda, Yussa; Munthasar Adha, Ariq; Iqbal, Muhammad (Universitas Medan Area, 2025)
This research focuses on the design and construction of an Arduino microcontroller-based robotic arm, using MPU6050 gyroscope and accelerometer sensors to mimic human hand movements. The goal is to improve efficiency and safety in industrial applications, especially for remote object manipulation in high-risk areas. The development process includes design, testing, and overcoming challenges such as sensor calibration and real-time response. The results show that the robotic arm is able to accurately follow human hand movements, offering a practical solution for industry. This research supports the development of adaptive and safe robotics technology in high-risk work environments.